2021
DOI: 10.21037/jtd-20-1752
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the outcomes of robotic segmentectomy and lobectomy

Abstract: Segmentectomy has gained popularity in the latest years as a valid alternative to lobectomy.Initially reserved to patient unfit for lobar lung resection, this procedure is now offered also in selected patient with <2 cm peripheral lung cancer confined to an anatomic segment with no nodal involvement on preoperative evaluation. The introduction of screening with low-dose CT chest scan allowed the identification of lung cancer at early stages, making possible to schedule a more conservative lung surgery.A major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 57 publications
0
14
1
Order By: Relevance
“…With the use of thoracic thin-section CT, the detection rate of pulmonary nodules increases, and some research results (1)(2)(3)(4)(17)(18)(19)(20)(21) have shown that the prognosis of segmentectomy is no worse than that of lobectomy in patients with metastatic lung tumors or early lung cancer. The JCOG0802 study is a randomized controlled trial to confirm whether segmentectomy is not inferior to lobectomy in regard to prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the use of thoracic thin-section CT, the detection rate of pulmonary nodules increases, and some research results (1)(2)(3)(4)(17)(18)(19)(20)(21) have shown that the prognosis of segmentectomy is no worse than that of lobectomy in patients with metastatic lung tumors or early lung cancer. The JCOG0802 study is a randomized controlled trial to confirm whether segmentectomy is not inferior to lobectomy in regard to prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In anatomical segmentectomy or subsegmentectomy, it is extremely important to master the types of the segmental and subsegmental bronchus. When planning a major lung resection the risk of conversion vary from 6.2% to 9.6%, being higher in video-assisted thoracic surgery (VATS) with unexpected bleeding as the leading cause (21,23). Accurate preoperative study (24,25) can reduce this risk to 2.6% and up to 0%, when a printed 3D model is available.…”
Section: Discussionmentioning
confidence: 99%
“…A more automated variation of VATS is a robotic operation [75] in which the surgeon controls the robotic arms with the surgical instruments using foot pedals and a console [76].…”
Section: Table 2 Comparision Of Histological Diagnoses In Patients Un...mentioning
confidence: 99%
“…The uptake of robotic lung resections has increased since its widespread introduction into clinical practice in 2009 and 2010, most rapidly in the South. 26,30,31 An estimated 20% or greater of all lobectomies are currently performed robotically (data not shown). The use of robotic lung resections in the VA is unknown and merits further study.…”
Section: Limitationsmentioning
confidence: 99%